ANALISIS DAMPAK PEMBEBANAN LEBIH TRANSFORMATOR TERHADAP PENYULANG SULAMADAHA GARDU GT-SOLBA TERNATE MALUKU UTARA - Latumahina, Ambraham; Launuru, Ari Permana (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
Analysis of the impact of transformer overload on the sulamadaha refeeddersa of the gt-solba ternate feeder north maluku, An overload transformer occurs in one of the distribution transformers at pt. Pln (persero) up3 ternate ulp ternate, namely the gt-solba distribution transformer in sulamadaha with a loading amount of 100,64% exceeding the standard set by spln which is 80%. This study aims to find a way to overcome the problem of overload in the gt-solba distribution transformer in sulang suladaha and also to get the load on the gt-solba distribution transformer before and after transferring the transformer load. Conducting this research using data collection methods by collecting data at ulp ternate, interviewing field supervisors and studying literature that supports problem solving in the gt-solba transformer. In solving. Therefore, in overcoming the problem of overload on the gt-solba transformer, improvements are made by looking at these conditions, one of which is by shifting the transformer load or switching the transformer power with the same capacity of 160 kva as the previous transformer of 160 kva. From the results of the load transfer, it was obtained that the loading results obtained the percentage value of the transformer loading before the transformer load was transferred, namely 100,64% and after the transformer load was transferred, namely 43,2%, so that it decreased by 56,8%. Which means that transformer load switching is one of the methods that can be used to overcome overload. Keywords: GT-SOLBA Transformer, Overloading, Sulamadaha Substation